Efficacy and tolerability of a low-glycemic-index ketogenic diet in Angelman syndrome: findings from the DIANE study - Iglesias Escalera, Gema; Cazorla Calleja, Rosario; Lorenzo Ruiz, María; Lara Herguedas, Julián; Gutiérrez Junquera, Carolina; Cilleruelo Pascual, María Luz; Caballero-Bermejo, Antonio F; Roman-Riechmann, Enriqueta; Pascual Pascual, Samuel Ignacio; Ruiz-Antorán, Belén (BMC, 2025)
Aim: This study evaluates the efficacy of a low-glycemic-index diet (LGID) in improving neurodevelopmental and sleep outcomes in pediatric Angelman Syndrome (AS) patients. Method: A prospective, evaluator-blinded cohort study was conducted with 20 pediatric patients (3-16 years) diagnosed with AS. Patients were assigned to an LGID or habitual diet group and followed for 24 weeks. The primary outcome was neurodevelopmental progress measured using the Bayley Scales of Infant and Toddler Development-III. Secondary outcomes included adaptive behavior (Vineland-II), gross motor function (GMFM-88), sleep quality (actigraphy and questionnaires), seizure frequency and a 30-min awake video-EEG. Results: At 24 weeks, the LGID group showed a trend toward improvement in cognitive and language domains, although differences were not statistically significant (p > 0.05). Qualitative EEG improvement was observed in 44% of LGID patients versus 25% in the control group. Sleep parameters showed minor changes, with no significant differences between groups. Interpretation: While the LGID was well-tolerated and showed trends toward neurocognitive and seizure improvements, results were not statistically significant. Further studies with larger sample sizes are needed.